Iterative joint precoder and decoder designs for multiuser AF wireless relaying systems - Chang, Kyungsik; Lim, Jaesung; Lee, Kanghee (2016 International Conference on Information and Communication Technology Convergence (ICTC), 2016)
An amplify-and-forward (AF) wireless relay strategies consisting of dispersed M sources, N relays, and M destinations all equipped with a single antenna is investigated in this paper. The salient objective of this paper is to determine jointly and iteratively the diagonal source-relay precoder and destination decoder matrices under the transmit power constraint at the both sources and relays based on a minimum mean square error (MMSE). Additionally, with the derived optimal matrices, the MMSE cost function behavior will be investigated numerically and analytically. Furthermore, an iterative algorithm is proposed to solve the desired optimization problem. In particular, the proposed scheme shows the best system performance among schemes presented in this paper. Finally, it is also shown that the MMSE cost function values are less than M at all times, regardless of N.